Geology, Structure, and Radiometric Age Determination of the Murowa Kimberlites, Zimbabwe - Moss S.; Marten B.; Felgate M.; Smith C.; Chimuka L.; Matchan E.; Phillips D. (My University, 2018)
The Murowa kimberlite field includes three diamondiferous kimberlite pipes (K1, K2, and K3) and multiple kimberlite dikes that have been emplaced into the Archean Chibi granite batholith north of the Limpopo belt in south-central Zimbabwe. Here we summarize the key aspects of the geology of the Murowa kimberlites from previous studies and integrate these findings with new structural data to interpret a structural model governing the locations, relative positions, and orientations of emplaced kimberlite. Key observations of drill core, thin section petrography, geochemistry, and mapping of exposed rocks at the Murowa diamond mine are summarized from previous work, and these data collectively form the basis for emplacement interpretations and three-dimensional (3-D) geologic models of each body. Structural observations are used to interpret the presence of a km-scale tensile bridge hosting the Murowa kimberlites and suggest Murowa is an example of kimberlite emplacement into multiple, reactivated, preexisting near-surface structures at different orientations. We propose that the physical state of the ascending magma (% of gas, extent of phase separation) can dictate whether kimberlite is emplaced along preexisting structures or creates and intrudes new fracture networks in planes of weak horizontal stress. A reproducible age of ~526 Ma is determined for two coherent kimberlite dikes at K1, while an older Rb-Sr model age of ~543 Ma is calculated for a single dike from K2, though this result is of limited reliability due to potential disturbance of the Rb-Sr system due to phlogopite alteration. These results highlight potential problems with reported ages from kimberlite pipes.
Keywords: Murowa kimberlite